Characerization of Geochemical Waste Rock on Indicate and Mitigation Acid Mine Drainage at Coal Mining Bukit Asam - Aida Syarif (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Acid mine drainage (AMD is a term generally used to describe infiltration of acid surface water in the mining areas. The study of the processs for formation acidmine drainage can be approached by two methods, the static and kinetic test. In the static test, that formed acidare determined by total sulphur content with an assumption that all sulphur contented in the stones are oxidized. While in the kinetic test, the acid are determined from is reaction stoichiometrically by using total both ion Fe2+ and H+, solved in the water as data in calculation. Kinetis test methods can be applicated with leached column test. Kinetic analysis of the test results on 5 samples of coal mine waste rock, it can be said that each of the rock samples as potentially acid forming rock it can be stated from the results of the analysis on pH value, content of Fe metal, ion sulfate and TSS of leachate obtained.